A method for predicting failure statistics for steady state elevated temperature structural components. (August 2021) - Nicolas, Andrea; Messner, Mark C.; Sham, T.-L.
Abstract: This paper presents the initial development of a high temperature life prediction method that accounts for the variability in the material properties of Grade 91 steel. The method accounts for material variability by fitting a variable 3-parameter Weibull distribution to experimental rupture data and accounts for the variability of creep deformation on the steady-state stresses via a Monte Carlo approach. To ensure reasonable computational times, the model represents the material as an extremely viscous Stokes fluid with a non-Newtonian viscosity, therefore solving the stress relaxation problem with a steady, static, instead of transient, analysis. The complete statistical analysis combines this model for creep deformation with a probabilistic model for creep rupture to evaluate the probability of premature failure for a set of sample problems, comparing the predicted failure statistics to the design life predicted by the ASME Boiler and Pressure Vessel Code rules. Highlights: Steady-state creep was modeled using Stokes flow with non-Newtonian viscosity. A probabilistic model for rupture was developed to account for material variability. The probabilistic model enables a comprehensive assessment of rupture life.